A Case for Using Genomics and a Bioinformatics Pipeline to Develop Sensitive and Species-Specific PCR-Based Diagnostics for Soil-Transmitted Helminths - Grant, Jessica R.; Pilotte, Nils; Williams, Steven A. (Frontiers in Genetics, 2019)
ABSTRACT The balance of expense and ease of use vs specificity and sensitivity in diagnostic assays for helminth disease is an important consideration, with expense and ease often winning out in endemic areas where funds and sophisticated equipment may be scarce. In this review we argue that molecular diagnostics, specifically new assays that have been developed with the aid of next generation sequence data and robust bioinformatic tools, more than make up for their expense with the benefit of a clear and precise assessment of the situation on the ground. Elimination efforts associated with the London Declaration and the World Health Organization (WHO) 2020 Roadmap have resulted in areas of low disease incidence and reduced infection burdens. An accurate assessment of infection levels is critical for determining where and when the programs can be successfully ended. Thus, more sensitive assays are needed in locations where elimination efforts are approaching a successful conclusion. While microscopy or more general PCR targets have a role to play, they can mislead and cause study results to be confounded. Hyper-specific qPCR assays enable a more definitive assessment of the situation in the field, as well as of shifting dynamics and emerging diseases.